THE NOTION OF TEACHING WRITING FOR STUDENTS (Conferencea, 2021)
Written speech is increasingly penetrating interpersonal and professional intercultural communication, in the process of teaching foreign languages, which can also be explained by the increasing role of information communication technologies in all spheres of human activity. This article tries to discuss the general methodological scientific literature views.